JUSTIVERSE: Utilization of Virtual Reality (VR) Technology in Learning Process and Moot Court Practice - Rahman Subha; Abdul Rahman; Aminuddin; Syarif Bahaudin Mudore; Deni Fikari (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2024)
Virtual reality is an interesting phenomenon in learning media studies. This is because individuals and groups are faced with technological sophistication that delivers online learning experiences that seem real. This study aims to describe the utilization of virtual reality (VR) technology in the learning process and moot court practices. The setting of this research is in the Department of Sharia, Economics, and Islamic Business of STAIN Majene. To reveal the phenomenon of VR-based learning, a qualitative approach with descriptive study method was used. The results of this study concluded that the application of VR technology can improve the quality of learning effectively. Through realistic simulations, students gain a more in-depth practical experience of the judicial process, which was previously difficult to obtain through conventional methods. VR provides a more interactive and inclusive learning experience and helps students to understand and master the material in a more efficient way.